The influence of oleic acid-propylene glycol mixture and iontophoresis to propranolol transdermal transport - Lucia Hendriati; Akhmad Kharis Nugroho (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2009)
Propranolol has an intensive first pass metabolism, resulted in a low oral bioavailability. One alternative to circumvent such problem is the delivery by transdermal route. The objective of this study was to evaluate the effect of oleic acid 10 % (in propylene glycol 20 %) as enhancer, with and without iontophoresis, on transdermal transport of propranolol. Propranolol delivery was examined based on the in vitro transport studies across the rat skin (after hair removal) in a vertical diffusion cells system. Skin was pretreated with the mixture of oleic acid 10 % (in propylene glycol 20 %) for 3 hours. Iontophoresis was performed at a current density of 0.25 mA/cm2 for 3 hours. Donor compartment was filled with propranolol solution (5 mg/mL in citric buffer pH 5), while the acceptor phase was filled with phosphate buffer saline at pH 7.4. The results indicate that the enhancement methods increase the transdermal penetration of propranolol (p<0.05). The flux without any enhancement methods was 13.16 ± 0.79 mg/cm2/hour. The flux with either oleic acid-propylene glycol pretreatment, iontophoresis or combination of both were 28.75 ± 3.04 mg/cm2/hour, 40.47 ± 5.78 mg/cm2/hour, and 85.42 ± 16.94 mg/cm2/hour respectively. Based on mathematics calculation, if an iontophoretic patch of 12 cm2 is used after skin pretreatment with oleic acid - propylene glycol mixture, the steady state plasma concentration of propranolol could reach 24.65 mg/mL. Therefore, therapeutic level might be achieved. This indicated a promising future of transdermal delivery of propranolol.Key words : propranolol, transdermal, enhancer